The Strategy of Empowerment Based on ESQ Power: A Social Innovation in The Poverty Overcoming - Peribadi, Peribadi (el Harakah: Jurnal Budaya Islam, 2017)
This research aimed to develop an innovation of empowerment strategy on ESQ Power – Based. It was designed through a phenomenology deductive, a case study and the methodof research and development or the procedure of member check. The three of them were used eclectically in order to design an ideal formulation. The research findings indicated that the actors and actresses of poverty overcoming in Kendari City have not had the emotional intelligence and spiritual intelligence yet as ESQ Power. As a result, they were not optimal in performing their duties, roles and responsibilities. Therefore, the urgency of empowerment paradigm on ESQ Power – Based that has been formulated and validated by the skillful validator must be used in the future to increase the sense of responsibility of the actor network in overcoming the pauperization and poverty. Penelitian ini bertujuan untuk mengembangkan sebuah inovasi strategi pemberdayaan berbasis ESQ Power. Hal itu dirancang melalui deduksi fenomenologis, studi kasus serta metode penelitian dan pengembangan atau prosedur member check. Ketiganya digunakan secara eklektik untuk merancang formulasi ideal. Temuan penelitian menunjukkan bahwa aktor dan aktris penanggulangan kemiskinan di Kota Kendari belum memiliki kecerdasan emosional dan kecerdasan spiritual sebagai ESQ Power. Akibatnya, mereka tidak optimal dalam menjalankan tugas, peran dan tanggung jawabnya. Oleh karena itu, urgensi paradigma pemberdayaan berbasis ESQ Power yang telah dirumuskan dan divalidasi oleh validator ahli tersebut harus mulai digunakan ke depan untuk meningkatkan rasa tanggung jawab jaringan aktor dalam mengatasi pemiskinan dan kemiskinan.